On a Particular Aspect of the Identification of Tibetan Xylographs: Preliminary Remarks on the Importance of Craftsmen - Michela Clemente (Kervan. International Journal of Afro-Asiatic Studies, 2017)
This essay briefly discusses the early history of Tibetan printing by comparing some facets of this subject with the European phenomenon. Printing started to be a means of dissemination of texts in Tibet and Europe at roughly the same time. Recent research indicates that although printing in Tibet does not seem to have had the kind of socially transformative effects highlighted in Elisabeth Eisenstein’s study, it did have some important consequences and also similarities with the European printing history. This article also presents a Marie Sklodowska Curie project on Tibetan xylographs entitled Tibetan Book Evolution and Technology (TiBET), which was carried out at the University of Cambridge (Mongolia and Inner Asia Studies Unit) from 2013 to 2015. This paper focuses in particular on one of the aspects of the above-mentioned project, that is to say, the craftsmen who worked on sixteenth century xylographs and their importance for the identification of Tibetan prints. These artists were allowed to sign their work, a peculiarity that was typical of the earliest stage of printing and is extremely relevant for locating the printing house where a certain xylograph was produced. By comparing the different signatures and patterns of carving, writing or drawing, we might learn to distinguish the diverse style of each artist. This would help us in identifying those who worked on xylographs that lack signatures and do not mention them in colophons. From these prints we can also extract information about the craftsmen and the printing projects with which they were associated.